Guideline development for the management of gout: role of combination therapy with a focus on lesinurad - Jones G; Panova E; Day R (Dove Medical Press, 2017)
Graeme Jones,1 Elena Panova,1 Richard Day2 1Menzies Institute for Medical Research, University of Tasmania, Hobart, TAS, Australia; 2University of New South Wales, Medicine, St Vincent’s Hospital, Sydney, NSW, Australia Abstract: The aim of this review was to summarize the evidence for combination therapy to achieve serum urate (SUA) target levels in gout. Within this overarching aim, a second aim was to evaluate the evidence for a new uricosuric agent lesinurad, which inhibits urate transport in the kidney. In summary, this review indicates that there are a number of ways to approach patients who do not achieve a target serum urate with allopurinol (APL) monotherapy. These include higher doses of APL up to 600–800 mg/d, switching to febuxostat, or adding in a uricosuric. For the latter option, controlled supporting evidence is available for benzbromarone, probenecid, and lesinurad. All options appear similar in terms of success rates, so the choice of option comes down to physician and patient choice, cost, experience, and strength of the evidence base. Increasing the dose of APL is the cheapest option, while febuxostat is consistently superior to standard doses of APL. The strongest evidence for the uricosuric option is available for lesinurad as trials of other agents are either nonexistent or based on small single-centre trials. It is suggested that guidelines should be expanded to consider all of these evidence-based options in the not-uncommon occurrence of APL inadequate response. Keywords: gout, therapy, combination, urate lowering